SOSIALISASI LEGALITAS USAHA BAGI PENGRAJIN ANYAMAN BAMBU DI DESA DUWET KECAMATAN TUMPANG KABUPATEN MALANG - Hudriyah Mundzir; Khrisna Hadiwinata; Shohib Muslim; Muhammad Akhlis Rizza; Moh. Abdullah Anshori; M. Nanak Zakaria (Jurnal Pengabdian kepada Masyarakat, 2023)
This service activity was carried out in Duwet Village, Tumpang District, Malang Regency, with the Duwet Village Head Partner. The Community Service Team found the condition of the Duwet Village BUMDes named Dewantara which was unable to maximize the potential of Duwet Village, the lack of understanding of BUMDes managers and the community about BUMDes management, and a lack of understanding about the importance of the legality of the business owned by Dewantara BUMDes, namely the woven bamboo craft business. Community service activities are carried out in 3 (three) stages, namely the preparation stage, the activity implementation stage (socialization, mentoring, and training), and the activity evaluation stage. The solutions we offer are 3 (three) aspects, namely social aspects, legal and economic aspects (capital), and aspects of service quality or social life. The method used in this community service activity is lecture and question and answer, namely the delivery of material about the meaning of business legality, procedures for obtaining business legality, trademark registration, MSMEs. . In addition to the lectures, discussions and questions and answers were also held to provide opportunities for participants consisting of BUMDesa administrators from Duwet Village, Wringinsongo Village and Tulusbesar Village. The result of this activity for participants is insight into business legality and various forms of business legality.